Engaging with ethics in Internet of Things: Imaginaries in the social milieu of technology developers. Issue 2 (October 2019) - Ustek-Spilda, Funda; Powell, Alison; Nemorin, Selena
Discussions about ethics of Big Data often focus on the ethics of data processing: collecting, storing, handling, analysing and sharing data. Data-based systems, however, do not come from nowhere. They are designed and brought into being within social spaces – or social milieu. This paper connects philosophical considerations of individual and collective capacity to enact practical reason to the influence of social spaces. Building a deeper engagement with the social imaginaries of technology development through analysis of two years of fieldwork with start-ups working on Internet of Things, this paper suggests that different action positions can emerge, with consequences for how data is understood and valued. The Disengaged, Pragmatist and Idealist ethical action positions identified in the paper reveal the ways individuals and groups negotiate possibilities for ethical action, through justifications, explanations and structuring of system features.